Pengaruh Penerapan Model Project Based Learning Terhadap Hasil Belajar Tematik Terpadu di Sekolah Dasar - Sari, Kurnia Nur'afita; Fitria, Yanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
The study is intended to describe the impact that application of the basea learning project (project) on learning integrated thematic results in elementary schools is quantitative In the form of quasy experimentation des ign with the non equnalent control group design. Technique Sampling of the chuster random sampling. The research subject is a student student of the visdn zero-one class, a city of wasteland. Research shows: the average pretest/experimental class that applies learning using the model project based learning is 50.42 and the average study posttest for experimental class testing is 85.76. Whereas the study in the control class the results of pretesr learning are 64.4 and the average learning results after cataloging using a conventional approach have a postest 69.19. Based on the hypothesis test done with test t, acquired t'= 6.42 > td2.0096. Thus the uodel project rased leatuing has hada significant impact on learning integrated tenatik in elementary school.